Properties of the Non-Homogeneous Gutter-Type Systems - Burokas, T.; Štaras, S. (Elektronika ir Elektrotechnika, 2005)
The gutter-type helical and meander traveling-wave deflecting systems, containing periodical non-homogeneities, caused by the special gap for the electron beam, are considered in order to reveal the influence of the non-homogeneities on properties of the systems. The multiconductor lines method is used for analysis of the systems. The models of the systems, containing segments of the shielded multiconductor lines, containing one row of conductors, are used. Dispersion equations and expressions for the input impedance of the systems are considered. Examples of the calculated characteristics (retardation factor and input impedance versus frequency) are presented and properties of the non-homogeneous gutter-type systems are revealed. The input impedance of the non-homogeneous gutter-type helical system changes with frequency less than the input impedance of the homogeneous gutter-type helical system. The dispersion of the retardation in the non-homogeneous gutter-type meander system is less than in the homogeneous gutter-type meander system. When frequency increases and the phase difference angle θ between the voltages or currents on the neighbor helical or meander wires approaches π , the non-homogeneous slow-wave structure obtains properties of the rejection filter. The width of the stopband is less and the characteristics of the non-homogeneous gutter-type systems become better when the dimensions of the special gap for the electron beam are less. Besides that, the structure of the deflecting electric field is considered. The strength of the deflecting field in the gutter-type systems changes with frequency less than in the helical and meander systems without the shields between the neighbor wires. According to simulation of dynamic characteristics of the traveling wave cathode-ray tubes, using the gutter-type systems, it is possible to avoid distortions, caused by retardation dispersion and input impedance change versus frequency. The dimensions of the gap for electron beam in the non-homogeneous gutter-type systems must be minimal. Ill. 9, bibl. 12 (in Lithuanian; summaries in Lithuanian, English, Russian).